Transformasi Tata Kelola Legislatif di Palembang Platform Legislasi Digital Terintegrasi - Muhammad Farhan; Sri Rahayu (CV. Shofanah Media Berkah, 2025)
Public information disclosure requires the Legal Documentation and Information Network (JDIH) to provide legal data services that are fast, accurate, and easily accessible. JDIH Palembang City, as a strategic instrument of governance, has a vision to realize integrated technology-based management. However, field observations identified significant operational challenges hindering the achievement of this vision. The main problems lie in the suboptimal archive digitization process, reliance on physical documents, and the risk of losing vital archive data. This research aims to address these problems by proposing a